The Future of Man is to be an Animal. : Readings of Aganben, Levi and Malaparte. - Álvarez, José Maurício (Advances in Social Sciences Research Journal, 2020)
This paper examines the role of the dog in the work of two modern Italian writers Curzio Malaparte and Carlo Levi and the writings of a notable Italian philosopher of our times, The Italian philosopher Giorgio Agamben, in several works he assures the importance of animals in tne human life, and the dog, in particular, in the redefinition of the future of the human being. Taking their assertions as analysis tools for the mentioned authors, we analize in the texts, where they formulate a peculiar way of central role represented by the animal. In Levi he is capable to be the key able to open the door to a fantastic world. For Malaparte the dog becomes the essential counterpart to the humanity being capable to harbor huge feelings that he is able to teach man . Finally, for Agamben, men and animals are part of the same natural creation and, eschatologically, walk together until, at the end of time, when humans will reconcile with their half animal nature.